Load intensity comparison of woman players aged 17-18 in competitive and warm-up matches in handball - Belka, J.; Hulka, K.; Svoboda, Z.; Kostelnik V. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The study analyzes load intensity of woman players aged 17-18 in competitive and warm-up matches in handball - team DHK Zora Olomouc. The load intensity results from both competitive and warm-up matches that are here compared. Three competitive and three warmup matches were analyzed. 12 players were monitored in each game. The goalkeepers were not involved. The maximum heart rate (HRmax) was defined by the help of Beep test.